Interpretasi Komprehensif Lafaz Bi 'Abdihi Pada QS. Al-Isra' Ayat 1: Telaah Penafsiran dalam Tafsir Al-Munir, Tafsir Al-Qur'an Al-'Adzhim dan Tafsir Al-Mishbah - Risky Risky; Nawir Yuslem (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This study aims to comprehensively examine the interpretation of lafaz bi 'abdihi in QS. al-Isra' [17]:1 through cross-tafsir analysis, namely al-Munir, Tafsir al-Qur'an al-'Adzhim by Ibn Katsir, and al-Mishbah by M. Quraish Shihab. The focus of this research is to uncover the meaning of ubudiyyah as the core of the spirituality of the Prophet Muhammad ﷺ as well as its relevance for the lives of contemporary Muslims. The method used is qualitative research with descriptive-analytical, comparative, and semantic approaches, while the data collection technique is done through library research on tafsir texts and supporting literature. The results showed that the three mufasirs have similarities in emphasizing that the glory of the Prophet lies in the identity of servanthood, not merely apostolic status. However, each tafsir has a different style: al-Munir emphasizes the fiqh-theological dimension, Ibn Katsir focuses on history, while al-Mishbah emphasizes spiritual context and social relevance. The synthesis of the three emphasizes that bi 'abdihi contains universal messages of humility, spiritual value-based leadership, and resistance to the challenges of modernity such as materialism and individualism. This research contributes to the strengthening of comparative tafsir studies while opening space for the integration of classical and contemporary tafsir with the needs of modern Muslims. The theoretical implications enrich the paradigm of ubudiyyah-based tafsir, while the practical implications are relevant for character education, social ethics, and Islamic leadership. Further research is suggested to link the study of tafsir with an interdisciplinary approach in order to expand the scientific horizon.